All binder-free electrophoresis deposition synthesis of nickel cobalt hydroxide/ultraphene and activated carbon electrodes for asymmetric supercapacitors. (20th May 2018) - Lai, He-Xin; Lin, Lu-Yin; Lin, Jeng-Yu; Hsu, Yu-Kai
Abstract: Electrophoresis deposition (EPD) is one of attractive methods for fabricating electrodes due to simple and cost-effective natures. All binder-free EPD process is used on preparing the nickel cobalt hydroxide and a commercial graphene (Ultraphene™) (Ni-Co-OH/U) electrode for asymmetric supercapacitors (ASC). The effects of EPD duration and potential as well as Ni:Co ratio in EPD solution on morphology of Ni-Co-OH/U and electrocapacitive performance of resulting electrodes are investigated. A high areal capacitance of 8.18 F cm −2 is obtained for the optimized Ni-Co-OH/U electrode fabricated using 10 min, 5 V and 1:2 as EPD duration, potential, and Ni:Co ratio in EPD solution, respectively, mainly due to its large surface area, suitable size of gaps as well as high electrical conductivity and low charge transfer resistance. The ASC shows a potential window of 1.4 V and a CF value of 222 mF g −1 . A maximum energy density of 23.4 W h kg -1 at the power density of 937.2 W kg −1 and the cycling stability with a CF retention of 56% after 3000 cycles repeated charge/discharge process are also attained. This work demonstrates the fleasibility of applying the effective all binder-free EPD process to fabricate efficient ASC composed of the metal hydroxide and carbon composite. Graphical abstract: Highlights: Binder-free electrophoresis deposition (EPD) is used on fabricating electrodes. Ni-Co-OH/Ultraphene (Ni-Co-OH/U) composite is made for asymmetric supercapacitors. The Ni:Co ratio in solution, the duration and the potential for EPD are optimized. An areal capacitance of 8.18 F cm −2 is got for the optimized Ni-Co-OH/U electrode. The asymmetric supercapacitor (ASC) shows a CF value of 222 mF g -1  at 20 mA cm −2 .